A Novel Single-Nucleotide Polymorphism in the Lactoferrin Gene Is Associated with Susceptibility to Diarrhea in North American Travelers to Mexico - Mohamed, Jamal A.; DuPont, Herbert L.; Jiang, Zhi Dong; Belkind-Gerson, Jaime; Figueroa, Jose Flores; Armitige, Lisa Y.; Tsai, An; Nair, Parvathy; Martinez-Sandoval, Francisco J.; Guo, Dong-chuan; Hayes, Patricia; Okhuysen, Pablo C. (Clinical infectious diseases, 2007)
Background. Diarrhea affects 40%–60% of travelers from industrialized nations who visit developing countries and is due to bacterial, viral, and parasitic agents. Lactoferrin is bactericidal to enteric pathogens, modulates the intestinal immune response, and is excreted in stool in response to infection with intestinal organisms. We investigated the impact that selected single-nucleotide polymorphisms (SNPs) in the human lactoferrin gene have on susceptibility to traveler's diarrhea. Methods. Adults who had recently arrived in Mexico were studied prospectively for the occurrence and causal agent(s) of traveler's diarrhea, and genotyping was performed for 9 distinct lactoferrin SNPs. Results. Of the 9 SNPs studied, only 1 SNP (located in exon 15) was associated with traveler's diarrhea (P = .004). When compared with healthy travelers, and after adjustment for known risk factors for traveler's diarrhea (such as age and duration and season of travel), subjects with the T/T genotype in amino acid position 632 were more likely to develop traveler's diarrhea (67% vs. 33%; relative risk [RR], 1.4; 95% CI, 1.2–1.7; P < .001), to have diarrhea with a pathogen identified (RR, 1.3; 95% CI, 1.1–1.6; P = .03), and to have a marker of intestinal inflammation in stool specimens (blood, mucus, or white blood cells; 52% vs. 38%; P = .036). The association was also significant when norovirus was not identified in stool samples (RR, 1.34; 95% CI, 1.06–1.34; P = .01). Conclusions. The T/T genotype in position codon 632 of the lactoferrin gene is associated with susceptibility to diarrhea in North Americans traveling to Mexico.